Cellular α-synuclein pathology is associated with bioenergetic dysfunction in Parkinson's iPSC-derived dopamine neurons. (11th February 2019) - Zambon, Federico; Cherubini, Marta; Fernandes, Hugo J R; Lang, Charmaine; Ryan, Brent J; Volpato, Viola; Bengoa-Vergniory, Nora; Vingill, Siv; Attar, Moustafa; Booth, Heather D E; Haenseler, Walther; Vowles, Jane; et al.
Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder and a central role for α-synuclein (αSyn; SNCA ) in disease aetiology has been proposed based on genetics and neuropathology. To better understand the pathological mechanisms of αSyn, we generated induced pluripotent stem cells (iPSCs) from healthy individuals and PD patients carrying the A53T SNCA mutation or a triplication of the SNCA locus and differentiated them into dopaminergic neurons (DAns). iPSC-derived DAn from PD patients carrying either mutation showed increased intracellular α Syn accumulation, and DAns from patients carrying the SNCA triplication displayed oligomeric α Syn pathology and elevated α Syn extracellular release. Transcriptomic analysis of purified DAns revealed perturbations in expression of genes linked to mitochondrial function, consistent with observed reduction in mitochondrial respiration, impairment in mitochondrial membrane potential, aberrant mitochondrial morphology and decreased levels of phosphorylated DRP1 Ser616 . Parkinson's iPSC-derived DAns showed increased endoplasmic reticulum stress and impairments in cholesterol and lipid homeostasis. Together, these data show a correlation between α Syn cellular pathology and deficits in metabolic and cellular bioenergetics in the pathology of PD.